A Heuristic Search Method Unified in Blockchain Expertise for Supply Chain Management - J. Jeyabharathi, S. Velliangiri, N. Nasurudeen Ahamed, P. Karthikeyan (International Journal of Control and Automation, 2020)
Blockchain is a distributed open (Public) ledger that is used to record the transaction across many computers. Blockchain technology can be applied in any domain such as banking, healthcare, real estate, travel, food, and supply chain. In supply chain management, blockchain technology also integrates the Artificial Intelligence (AI). Artificial Intelligence empowers placing that information quickly without quite a bit of human efforts. Blockchain and artificial intelligence advancements, when executed together, might draw out a change that can be named as progressive in the field of innovation. AI, on the other hand, to find the optimal path in the commodities, we present the heuristic search method for the supply chain vehicle.